The Population Cost‐Effectiveness of Weight Watchers with General Practitioner Referral Compared with Standard Care. Issue 8 (23rd August 2018) - Lymer, Sharyn; Schofield, Deborah; Cunich, Michelle; Lee, Crystal Man Ying; Fuller, Nicholas; Caterson, Ian; Colagiuri, Stephen
Abstract : Objective: This study aimed to assess population‐level cost‐effectiveness of the Weight Watchers (WW) program with doctor referral compared with standard care (SC) for Australian adults with overweight and obesity. Methods: The target population was Australian adults ≥ 20 years old with BMI ≥ 27 kg/m 2, whose obesity status was subsequently modeled for 2015 to 2025. A microsimulation model (noncommunicable disease model [NCDMod]) was used to assess the incremental cost‐effectiveness of WW compared with SC. A health system perspective was taken, and outcomes were measured by obesity cases averted in 2025, BMI units averted for 2015 to 2025, and quality‐adjusted life years for 2015 to 2025. Univariate sensitivity testing was used to measure variations in the model parameters. Results: The WW intervention resulted in 60, 445 averted cases of obesity in 2025 (2, 311 more cases than for SC), extra intervention costs of A$219 million, and cost savings within the health system of A$17, 248 million (A$82 million more than for SC) for 2015 to 2025 compared with doing nothing. The modeled WW had an incremental cost‐effectiveness ratio of A$35, 195 in savings per case of obesity averted in 2025. WW remained dominant over SC for the different scenarios in the sensitivity analysis. Conclusions: The WW intervention represents good value for money. The WW intervention needs serious consideration in a national package of obesity health services. Abstract : See Commentary, pg. 1253 .